A novel loss-of-function variant in STAT1 causes Mendelian susceptibility to mycobacterial disease - Lv, Kunlun; Gong, Zhuoqing; Fu, Yiting; Zhao, Sisi; Song, Yinggai; Wang, Huijun; Lin, Zhimiao (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMendelian Susceptibility to mycobacterial disease (MSMD) is a rare inherited immunodeficiency disorder characterized by increased susceptibility to atypical mycobacterial infections induced by defective IFN-γ pathway.MethodsWe report three patients from a family presenting with multiple osteolytic lesions and cutaneous granulomas due to Mycobacterium marinum infections. Functional studies, including Western blotting and immunofluorescence, assessed phosphorylation and nuclear translocation of the mutant STAT1-Ile707Thr in eukaryotic overexpression systems. A luciferase reporter assay evaluated its transcriptional activity. Additionally, structural analysis using AlphaFold3 predicted the variant’s functional impact.ResultsA novel STAT1 variant (c.2120T>C, p.Ile707Thr) was identified. The STAT1-Ile707Thr mutant exhibited reduced phosphorylation and impaired nuclear translocation compared to wild-type STAT1. The luciferase assay confirmed decreased transcriptional activity. AlphaFold3-based cluster analysis supported a loss-of-function effect of the mutant.DiscussionThis study expands the spectrum of STAT1 variants and microbial pathogens associated with MSMD.